2011
DOI: 10.1590/s0004-282x2011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Paced auditory serial addition test (PASAT): a very difficult test even for individuals with high intellectual capability

Abstract: Objective: To assess the difficulty of paced auditory serial addition test (PASAT) in a population of high intellectual level, under ideal cognitive testing circumstances. Method: One hundred medical students underwent PASAT testing. They had slept well the night before, they had eaten before the assessment, they were not using any drugs that could affect the central nervous system and they did not have depression, anxiety or any chronic disease. Results: The average result from the three-second version of PAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…In the control group, 3 subjects (5.3%) decided not to complete PASAT3 even though they completed SDMT. These data support previous findings in a general population regarding difficulties in answering items in PASAT, even in ideal conditions [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the control group, 3 subjects (5.3%) decided not to complete PASAT3 even though they completed SDMT. These data support previous findings in a general population regarding difficulties in answering items in PASAT, even in ideal conditions [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…PASAT is part of the Multiple Sclerosis Functional Composite (MSFC), developed to measure impairment and disability in MS [ 13 ], and it is widely used in clinical research. Despite its extensive use, Brooks et al showed that results are inadequate even in young and intellectually active subjects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…27 Our results showed similar performances of participants with MS and the comparison group on PASAT. 46 It must be taken into account that in the present study, depression was assumed to be a confounding factor and the participants with MS had mild disability (EDSS < 3.5) and some were in the early stages of disease. 27,45 These discrepancies in the literature may be related to the effect of confounding factors, stages of disease, intelligence, and mathematical ability.…”
Section: Discussionmentioning
confidence: 95%
“…No test probes working memory apart from the PVSAT and here the 2 s version lacked sensitivity in discriminating between disease types. This failure probably reflects the difficulty of the task, which has also proved challenging to healthy control subjects . It is important to note that whilst the computerized battery is able to distinguish between the four disease types studied here, it not does capture the full range of cognitive sequelae associated with MS and therefore should be viewed as a screening measure only.…”
Section: Discussionmentioning
confidence: 92%